2017
DOI: 10.3390/polym9050180
|View full text |Cite
|
Sign up to set email alerts
|

Glass Fiber Reinforced Polymer (GFRP) Bars for Enhancing the Flexural Performance of RC Beams Using Side-NSM Technique

Abstract: Reinforced concrete (RC) structures require strengthening for numerous factors, such as increased load, modification of the structural systems, structural upgrade or errors in the design and construction stages. The side near-surface mounted (SNSM) strengthening technique with glass fiber-reinforced polymer (GFRP) bars is a relatively new emerging technique for enhancing the flexural capacities of existing RC elements. Nine RC rectangular beams were flexurally strengthened with this technique and tested under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 41 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…From the crack location, symmetric distribution was presented. e failure mode of CB-2 is similar to the reinforcement concrete beams' failure mode in bending with GFRPS [28] or CFRPS [29]. (Table 8) showed that the use of NSM screw-thread steels and NSM …”
Section: Specimen Cb-3mentioning
confidence: 71%
See 2 more Smart Citations
“…From the crack location, symmetric distribution was presented. e failure mode of CB-2 is similar to the reinforcement concrete beams' failure mode in bending with GFRPS [28] or CFRPS [29]. (Table 8) showed that the use of NSM screw-thread steels and NSM …”
Section: Specimen Cb-3mentioning
confidence: 71%
“…Flexural cracks are present in the vertical stone slab surface direction. Crack formation process is similar to concrete members [21][22][23][24][25][26][27][28][29]. e following section presents the detailed failure progress and failure mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e greater confinement granted by the adhesive and the surrounding concrete is considered the best advantage provided by the NSM method [2]. is strengthening technique has already been proven to be effective for the shear strengthening [3][4][5][6] and flexural strengthening of RC beams [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Many studies have used conventional steel bars instead of FRP materials for beam strengthening by employing the NSM method [21,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have applied the NSM FRP strengthening method to improve the flexural and shear strength of RC beams [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], whilst others have used conventional steel bars instead of FRP materials for flexural and shear strengthening [21][22][23][24][25][26][27][28]. However, only few of these studies have focused on torsion strengthening [29][30][31]32] and no previous work has investigated the application of conventional steel bars for the torsion strengthening of RC beams.…”
Section: Introductionmentioning
confidence: 99%